1998
DOI: 10.1118/1.598356
|View full text |Cite
|
Sign up to set email alerts
|

Optical CT reconstruction of 3D dose distributions using the ferrous–benzoic–xylenol (FBX) gel dosimeter

Abstract: In recent years, magnetic-resonance imaging of gelatin doped with the Fricke solution has been applied to the direct measurement of three-dimensional (3D) radiation dose distributions. However, the 3D dose distribution can also be imaged more economically and efficiently using the method of optical absorption computed tomography. This is accomplished by first preparing a gelatin matrix containing a radiochromic dye and mapping the radiation-induced local change in the optical absorption coefficient. Ferrous-Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
142
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 25 publications
4
142
1
2
Order By: Relevance
“…Any system that is to be considered a suitable dosimeter has to fulfill acceptable characteristics of reproducibility and independence with the radiation beam quality 4 , 6 , 33 , 36 , 37 . These were tested to judge if the new solution is applicable in low‐dose‐level dosimetry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any system that is to be considered a suitable dosimeter has to fulfill acceptable characteristics of reproducibility and independence with the radiation beam quality 4 , 6 , 33 , 36 , 37 . These were tested to judge if the new solution is applicable in low‐dose‐level dosimetry.…”
Section: Methodsmentioning
confidence: 99%
“…Investigations are carried out by modifying the system dedicated to relative high doses by incorporating chemical components, like benzoic acid 3 , 9 , 31 , 32 , 33 in its preparation. Comparisons between the developed FXG system with conventional dosimetry systems are accomplished with the aim of validating it as a reliable dosimetry system.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, our hybrid optical imaging technique is quite different in physics from those pure optical imaging techniques. In those applications, the scanning beam is a laser beam and the projection data are the intensity of the transmitted ballistic light, which cannot penetrate relatively thick biological tissues.…”
Section: Fig 3 Experimental Results In the Reflection-detection Confmentioning
confidence: 99%
“…221,222 The practical implication is that Fricke gel dosimeters must be scanned within 2 h postirradiation, presenting logistical difficulties in a clinical setting. Most Fricke gel dosimetry has utilized MR as the readout method; however, Kelly et al 204 introduced xylenol-orange dye to create a Fricke gel compatible with optical-CT imaging. Recently, a promising new radiochromic material, PRESAGE, 223 has been introduced and detailed studies of the basic dosimetric properties have confirmed its promise for 3D dosimetry.…”
Section: Vb2 Fricke and Radiochromic Gels And Plasticsmentioning
confidence: 99%
“…Recently, new 3D dosimetry materials have been proposed with striking performance characteristics. 204,205 The three principal categories of 3D dosimeters are polyacrylamide ͑PAG͒ gels, 206 Fricke gels, 204 and radiochromic plastics, 205 and the two main methods of dose-readout are magnetic resonance ͑MR͒ imaging 207,208 and optical-computedtomography ͑optical-CT͒. 203,204,209 Other readout techniques are under evaluation, including x-ray-CT and ultrasound, but are not discussed further here as they are more preliminary.…”
Section: Vb Three-dimensional Detectorsmentioning
confidence: 99%